The Creation of a Dementia-friendly Community in Aged Residential Care: A Critical Realist Case Study - Shannon, Kay (Auckland University of Technology, 2021)
The practice of segregating people who require specialist dementia services from residents requiring other levels of care is beginning to be questioned. The ageing of the population, along with the accumulation of long-term health conditions such as dementia in older people indicate there will be an increasing demand for Aged Residential Care facilities. There is a growing awareness of the need to transform Aged Residential Care facilities into places where people can continue to live in ways that matter to them and engage in activities they value, with support. This thesis explains the transition of residents from a traditional Aged Residential Care facility to an innovative dementia-friendly village where they are supported to live life as normally as possible. Additionally, residents who require specialist dementia services are not segregated from the rest of the community within the secure perimeter. The case study, guided by a critical realist theoretical perspective, explains the process and outcomes of the transition of residents from Whare Aroha CARE to The CARE Village. Data for the study comprised transcripts of semi-structured interviews, records of observation of resident daily life, documents and photographs. Forty-two facility staff, residents, their family members and key informants participated in the study. Analysis of study data using a process of retroduction enabled three underlying mechanisms generating the events contributing to the process of the transition to be identified. These are 'they changed the culture of the workplace to enable person-centred care,' 'they created a physical environment that supports the vision of people living normal lives,' and 'they formed a governance network to support the transition to an innovative model of care.' Themes in the data explain the outcomes of the transition for the staff, residents and their family members. Data analysis began with the development of codes derived from the beginning theoretical propositions for the study and the data, themes were developed from those codes. Generative mechanisms, causing significant events, were identified by a process of retroduction, using the study themes and relevant theoretical and empirical literature. Three generative mechanisms, acting beneath the surface of events, enabled the transition of residents from Whare Aroha CARE to The CARE Village. Each of the generative mechanisms was an essential part of the process of the transition, accomplished at the intersection of workplace culture change, the development of a supportive physical environment and the support of a network of government officials. The development of an innovative dementia-friendly village was experienced differently by each of the three embedded units of analysis in the case study, the residents of the village, their family members and facility staff. The CARE Village residents transitioned to live in small houses, decorated in familiar styles, providing them with cues for daily living. Their participation in activities they value is supported by staff who know them well and understand how to help them to do as much as they can for themselves. Family members feel welcome in the normalised environment and confident their relatives are receiving appropriate care. Technology enables those people who require a secure environment to be free within the perimeter of the village. The thesis represents an explanation of the process and outcomes of developing a dementia-friendly village inspired by De Hogeweyk in the Netherlands, adapted to the New Zealand context. Specifically, the thesis makes a novel contribution to knowledge by explaining the complex intersection of workplace culture change, change in the physical environment and support from government officials that enabled the development of The CARE Village. The findings regarding the outcomes of the transition are novel in that they relate to the first village of its kind in New Zealand and explain how staff work together to support residents to live their lives in ways they value. Of particular significance is the finding that the development of a dementia-friendly village in ARC has enabled desegregation of residents who require specialist dementia services, and their safe integration into The CARE Village. The most significant original contribution to knowledge that the thesis makes is the contribution to theory on governance networks in public policy, in the context of person-centred care delivery in Aged Residential Care, and the national contract between aged care providers and District Health Boards.
Keywords: Aged care; Aged residential care; Dementia; Dementia-friendly communities; Person-centred care; Culture change; Governance networks; Innovation in aged care; Critical realism; Case study; Dementia-enabling environments; Desegregation